Trends in distribution, abundance and habitat features of skylark (Alauda arvensis) in northern Italy - de Carli, E; Fornasari, L; BANI, LUCIANO; BOTTONI, LUCIANA (OFFICE NATIONAL CHASSE, 1998)
The skylark, Alauda arvensis, has recently encountered a negative trend both in abundance and distribution over the whole of Europe. in order to investigate whether such a kind of trend might also be observed in Lombardy: Northern Italy we analysed counts performed both in the breeding season and in winter during common bird surveys based on randomly selected point counts. On the basis of the resulting data-base comprising about 10,000 point counts, we evaluated skylark distribution and abundance at the regional scale, that is on 23,842 km(2), and confirmed the general negative European trend. Despite the presence of local breeding populations in the alpine grassland, the highest numbers of skylarks were recorded in the lowland agricultural landscapes. In a range of altitudes between 8 and 350 m a.s.l., the highest wintering and breeding densities and the smallest population decrease in the breeding season were found at altitudes lower than 50 m a.s.l., over characteristic brown calcareous soils and rendzinas. A smal-scale study in an "increasing population" lowland area showed a strong preference for grassland habitats. Settlements on mowing and corn fields occurred later and these habitats were vacated earlier.